Diversity and Characterization of Multicellular Magnetotactic Prokaryotes From Coral Reef Habitats of the Paracel Islands, South China Sea - Teng, Zhaojie; Zhang, Yuyang; Zhang, Wenyan; Pan, Hongmiao; Xu, Jianhong; Huang, Hui; Xiao, Tian; Wu, Long-Fei (Frontiers in Microbiology, 2018)
While MMPs are ubiquitous in marine environments, the diversity of multicellular magnetotactic prokaryotes (MMPs) in sediments of coral reef ecosystems has rarely been reported. In this study we made an investigation on the diversity and characteristics of MMPs in sediments at 11 stations in coral reef habitats of the Paracel Islands. The results showed that MMPs were present at 9 stations, with spherical mulberry-like MMPs (s-MMPs) found at all stations and ellipsoidal pineapple-like MMPs (e-MMPs) found at 7 stations. The maximum abundance of MMPs was 6 ind./cm3. Phylogenetic analysis revealed the presence of one e-MMP species and 5 s-MMP species including 2 species of a new genus. The results indicate that coral reef habitats of the Paracel Islands have a high diversity of MMPs that bio-mineralize multiple intracellular chains of iron crystals and play important role in iron cycling in such oligotrophic environment. These observations provide new perspective of the diversity of MMPs in general, and expand knowledge of the occurrence of MMPs in coral reef habitats.